Shadow Libraries : Access to Knowledge in Global Higher Education - Karaganis, Joe (Book collections on Project MUSE., 2018)
This collection looks at how university students in Russia, Argentina, South Africa, Poland, Brazil, India, and Uruguay get the books and articles they need for their education. The death of Aaron Swartz and the more recent controversy around the SciHub and Libgen repositories have drawn attention to the question of access to knowledge, particularly for students facing financial and other constraints. Open access currently provides a very limited answer to this question, which piracy answers more comprehensively. This edited volume explores how access to knowledge has changed in the past twenty years, as student populations have boomed and as educators and publishers navigated the transition from paper to digital materials. It is concerned primarily with the experience of developing countries, where growing numbers of students, rapid development of Internet and device infrastructures, and high relative inequality have produced the sharpest tensions in the publishing and educational ecosystem.